Design of green infrastructure for the revaluation of the Ventanilla-Peru wetlands and the protection of the environment - Esenarro, Doris (2022)
The purpose of this research is the design of a green infrastructure that allows a regional conservation area to revalue the Ventanilla wetlands to promote ecotourism through spaces for the conservation of natural resources, turning it into a tourist attraction. The proposal considers design and construction criteria with adequate technology, biodegradable, and sustainable materials where environmental impact is minimized in this context. The collection of information through field visits and the use of different software for the topographic survey. Results show that the infrastructure design proposed was validated by a survey of potential users of the place, with 75% of the interviewees agreeing with the design proposal that allows interaction and harmony with nature, giving it a landscape value, generating local, national, and international visitors. The value is in the ecosystem services that the landscape provides to the city due to the design and construction criteria with adequate technology, biodegradable, and sustainable materials minimizing the environmental impact and promoting the cultural exchange, preservation, and ecological awareness wetland.